2014
DOI: 10.1021/la503775f
|View full text |Cite
|
Sign up to set email alerts
|

Particle Placement and Sheet Topological Control in the Fabrication of Ag–Hexaniobate Nanocomposites

Abstract: Synthetic methods are demonstrated that allow for the fabrication of Ag-hexaniobate nanocomposites with directed nanoparticle (NP) placement and nanosheet morphological control. The solvothermal treatment of exfoliated nanosheets (NSs) in the presence of Ag NPs leads to a high yield of Ag nanocomposites. This approach is quite flexible and, with control of time and temperature, can be used to produce nanocomposites with specific architectures; Ag NPs can be attached to nanosheets, attached to the surfaces of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 60 publications
(80 reference statements)
0
15
0
Order By: Relevance
“…Nanopeapods (NPPs) are a unique type of composite nanoarchitecture in which nanoparticles are captured by scrolling layers of exfoliated nanosheets to form linear assemblies in the hollow inner core [61][62][63][64][65][66]. NPPs offer advanced, precise techniques for engineering the exfoliation, scrolling, and assembly processes, and represent a promising alternative for the placement of the catalytic, magnetic, or other types of NPs [63].…”
Section: Hexaniobate Nanopeapodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanopeapods (NPPs) are a unique type of composite nanoarchitecture in which nanoparticles are captured by scrolling layers of exfoliated nanosheets to form linear assemblies in the hollow inner core [61][62][63][64][65][66]. NPPs offer advanced, precise techniques for engineering the exfoliation, scrolling, and assembly processes, and represent a promising alternative for the placement of the catalytic, magnetic, or other types of NPs [63].…”
Section: Hexaniobate Nanopeapodsmentioning
confidence: 99%
“…We have previously reported on the synthesis of hexaniobate-based NPPs incorporating nanoparticles such as Ag, Au, and CeO 2 , which showed interesting optical properties and feature materials that are relevant to catalytic applications [64][65][66]. Chen et al recently reported on the formation of Au@Nb@H x K 1−x NbO 3 NPPs that displayed high catalytic activity for photoelectrochemical water splitting over a broad spectral range under an applied external voltage.…”
Section: Hexaniobate Nanopeapodsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Furthermore, the dispersion of Nb 6 O 17 NSs can be varied in various solvents with different pH values and nanopeapods could be formed by additionally mixing some metal nanoparticles via solvothermal treatment. 15,16 Different exfoliation agents like tetrabutylam-monium and water attached on the surface of exfoliated oxide NSs would lead to distinct optical response time to some vapors. 17 Despite all of these, it is still a challenge to investigate the layer structure of the NSs, the interaction between the NSs and the dielectric medium or the ligands in a dielectric solvent environment, which is of great significance for solutionprocessing fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that the difference in surface atomic densities on both sides of single Nb 6 O 17 NSs creates a strain force, promoting NSs curl spontaneously . Furthermore, the dispersion of Nb 6 O 17 NSs can be varied in various solvents with different pH values and nanopeapods could be formed by additionally mixing some metal nanoparticles via solvothermal treatment. , Different exfoliation agents like tetrabutylammonium and water attached on the surface of exfoliated oxide NSs would lead to distinct optical response time to some vapors …”
Section: Introductionmentioning
confidence: 99%